2011
DOI: 10.1371/journal.pone.0027663
|View full text |Cite
|
Sign up to set email alerts
|

Celestial Moderation of Tropical Seabird Behavior

Abstract: Most animals, including birds, have cyclic life histories and numerous studies generally conducted on captive animals have shown that photoperiod is the main factor influencing this periodicity. Moon cycles can also affect periodic behavior of birds. Few studies have investigated the influence of these environmental cues in natural settings, and particularly in tropical areas where the change in photoperiod is slight and some bird species keep cyclic behaviors. Using miniaturized light sensors, we simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 64 publications
4
40
0
1
Order By: Relevance
“…When compared to other larger Procellariidae, such as different species of albatrosses, the Bugio petrel presented activity patterns only similar to those of the grey-headed albatross Thalassarche chrysostoma (Mackley et al 2010). With regard to the Bugio petrels' behaviour at night and its relation to the lunar cycle, we observed that these birds would spend more time in flight at night at times closer to the full moon; this is consistent with other species such as Barau's petrel Pterodroma baraui (Pinet et al 2011a), the streaked shearwater Calonectris leucomelas (Yamamoto et al 2008) and other larger species such as the white-chinned petrel Procellaria aequinoctialis (Mackley et al 2011). Bugio petrels could benefit from the increased visibility caused by the full moon to actively search for prey, therefore shifting from their 'sit and wait' foraging behaviour to 'active foraging' during these special days.…”
Section: Activity Patternssupporting
confidence: 83%
“…When compared to other larger Procellariidae, such as different species of albatrosses, the Bugio petrel presented activity patterns only similar to those of the grey-headed albatross Thalassarche chrysostoma (Mackley et al 2010). With regard to the Bugio petrels' behaviour at night and its relation to the lunar cycle, we observed that these birds would spend more time in flight at night at times closer to the full moon; this is consistent with other species such as Barau's petrel Pterodroma baraui (Pinet et al 2011a), the streaked shearwater Calonectris leucomelas (Yamamoto et al 2008) and other larger species such as the white-chinned petrel Procellaria aequinoctialis (Mackley et al 2011). Bugio petrels could benefit from the increased visibility caused by the full moon to actively search for prey, therefore shifting from their 'sit and wait' foraging behaviour to 'active foraging' during these special days.…”
Section: Activity Patternssupporting
confidence: 83%
“…These significant periodicities are not unlike the period (range = 29.3-29.8 days) and semiperiod (range = 14.6-14.9 days) of the lunar illumination cycle (i.e., synodic cycle). Periodicities in these ranges are not entirely unexpected given the growing number of studies demonstrating that lunar illumination is strongly correlated with a variety of organismal behaviors including animal movement (e.g., Larkin and Keeton, 1978;Grau et al, 1981;Baird et al, 2003;Tsukamoto et al, 2003;DeVries et al, 2004;Fraser, 2006;Pinet et al, 2011;Erisman et al, 2012;Schmidt et al, 2012;Sudo et al, 2014).…”
Section: Timing Of Route Fidelity Movementsmentioning
confidence: 91%
“…Decreased lunar light is correlated with increased number of departures during fall migration of land birds [56]. The arrival date of Barau's petrel (Pterodroma baraui), a tropical seabird, to their breeding colonies, occurred around the last full Moon of the austral (Southern Hemisphere) winter, and their night-time sea activity exhibited a clear cycle of about 29 days, with higher activity during full Moon nights, suggesting that nocturnal foraging is regulated by Moon phase [57].…”
Section: (C) Birdsmentioning
confidence: 99%